Hippocampal volume is more related to patient-reported memory than objective memory performance in early multiple sclerosis. (April 2021) - Glukhovsky, Lisa; Brandstadter, Rachel; Leavitt, Victoria M; Krieger, Stephen; Buyukturkoglu, Korhan; Fabian, Michelle; Sand, Ilana Katz; Klineova, Sylvia; Riley, Claire S; Lublin, Fred D; Miller, Aaron E; Sumowski, James F
Background: When persons with multiple sclerosis (MS) report memory decline but objective memory performance is normal, there is a bias toward believing objective test results. Objective: Investigate whether subjective memory decline or objective memory performance is more related to hippocampal and hippocampal subfield volumes in early MS. Methods: Persons with early MS ( n  = 185; ⩽5.0 years diagnosed) completed a subjective memory questionnaire; an objective memory composite was derived from four memory tests. Total hippocampal and subfield volumes were derived from high-resolution 3.0 T magnetic resonance images (MRIs). Partial correlations assessed links between hippocampal volumes and both subjective and objective memory, controlling for age, sex, mood, and pre-morbid intelligence quotient (IQ). Results: Lower total hippocampal and CA1 volumes were related to worse subjective memory but not objective memory (controlling for multiple comparisons). Correlations between subjective memory and both CA1 and subiculum were significantly stronger than were correlations between objective memory and these subfields. Patients in the worst tertile of subjective memory complaints (but not objective memory) had lower hippocampal volumes than 35 demographically similar healthy controls. Conclusion: Patient-report is inherently a longitudinal assessment of within-person memory change in everyday life, which may be more sensitive to subtle disease-related changes than cross-sectional objective tests. Findings align with the aging literature.